301 Antitumor Efficacy of Anti-PDL-1 In ACTH-Secreting Pituitary Adenomas: A Novel Immunotherapeutic Approach for Cushing's Disease. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Kemeny, Hanna; Elsamadicy, Aladine A; Farber, S. Harrison; Chongsathidkiet, Pakawat; Dechant, Cosette; Shen, Steven; Dunn, Ian F; Fecci, Peter E
Abstract: INTRODUCTION: Cushing's disease (CD), caused by ACTH-secreting pituitary adenomas, is a highly morbid condition with few treatment options beyond surgery and radiotherapy. Furthermore, 25% of patients prove refractory to standard of care. We and our collaborators recently reported expression of PDL-1 on human pituitary adenomas, providing a viable and novel immunotherapeutic target. Here we test anti-PDL-1 in vivo in a recapitulative murine model of CD. METHODS: PDL-1 on human ACTH-secreting adenomas was further assessed via IHC. The murine ACTH-secreting ATT20/D16v.2 adenoma cell line was utilized to establish subcutaneous and intracranial models of CD in syngeneic A/HeJ − C57L/J F1 or nude athymic mice. Tumor PDL-1 was assessed by flow cytometry and IHC. Plasma ACTH was measured by ELISA in subcutaneous models. Mice were treated intraperitoneally with anti-PDL1 or isotype every 3 d × 12 doses. For subcutaneous tumors, tumor volume and plasma ACTH were assessed, while survival was evaluated in the intracranial model. Tumor-infiltrating lymphocytes (TILs) were harvested and analyzed by flow cytometry. RESULTS: Human pituitary adenomas demonstrate significant (>1% staining) PD-L1 expression in 32% of samples, including 22% of ACTH-secreting adenomas. Murine ATT20/D16v.2 tumors also demonstrate elevated PD-L1 expression, as well as elevated plasma ACTH, recapitulating CD. Anti-PDL1 treated mice demonstrated reductions to tumor volume ( P = .0069, unpaired t test) in the subcutaneous model as well as long-term survival in the intracranial model. TILs in treated mice expressed lower levels of the exhaustion markers PD-1, TIM-3, and LAG-3. Accordingly, anti-PDL-1 efficacy was lost in athymic mice, revealing a T-cell-dependent treatment benefit. CONCLUSION: PDL-1 is significantly elevated on ACTH-secreting pituitary adenomas in patients and mice, yielding a significant T-cell dependent antitumor effect to treatment with anti-PDL1. These results demonstrate an appropriate murine model for preclinical investigation and a promising immunotherapeutic approach for CD. A multi-institution clinical trial is planned.